A state-of-the-art review: Near-surface mounted FRP composites for reinforced concrete structures. (10th June 2019) - Al-Saadi, Nihad Tareq Khshain; Mohammed, Alyaa; Al-Mahaidi, Riadh; Sanjayan, Jay
Highlights: NSM FRP system has gained considerable popularity worldwide. This paper reviews current research on concrete members retrofitted by NSM FRP system. The review focuses on the bond characteristics between NSM FRP, adhesive and concrete. Abstract: The use of fibre reinforced polymer (FRP) in civil construction applications with near-surface mounted (NSM) method has gained considerable popularity worldwide and can produce confident strengthening and repairing systems for existing concrete structures. The response of concrete structural members rehabilitated using FRP with externally-bonded (EB) method under monotonic and fatigue loading has been well reported. On the other hand, the monotonic and fatigue response of NSM FRP-rehabilitated concrete structures is less known. This paper reviews current research on concrete members retrofitted by NSM FRP system and exposed to monotonic and fatigue loading. It provides an outline of FRP composites and the fatigue behaviour of concrete, steel and FRP materials. In addition, the review focuses on the bond characteristics between NSM FRP, adhesive and concrete substrate, and on the flexure behaviour of NSM FRP-strengthened and repaired reinforced concrete (RC) beams. Furthermore, the paper reviews the failure modes, factors affecting NSM FRP systems, guidelines and codes for the use of FRP in concrete structures, damage accumulation and residual strength, stress limits in steel reinforcement, and the limitations of using epoxy and polymer-based cementitious adhesives for the strengthening of concrete members.